The Legality of Alfamart Acquisition of Lawson: Driving Into the Process With a GMS - Darminto Hartono; Anisyah Rani (Pena Justisia: Media Komunikasi dan Kajian Hukum, 2025)
Acquisition is a form of corporate action that has a significant impact on the control structure in a company and generally requires the approval of the General Meeting of Shareholders (GMS) as stipulated in Law Number 40 of 2007 concerning Limited Liability Companies (UUPT). However, in practice, not all acquisitions follow this normative flow. This study discusses the legality of the acquisition process carried out by Alfamart against Lawson without going through the GMS mechanism. Using a juridical-normative approach, this article analyzes the provisions of the UUPT and derivative regulations from the Financial Services Authority (OJK), especially POJK Number 17/POJK.04/2020 and POJK Number 42/POJK.04/2020. The results of the study show that even though it did not go through the GMS, the acquisition was still legally valid because it met the exception requirements, namely the transaction value is below 50% of the total equity and the affiliate relationship does not cause a conflict of interest. Thus, Alfamart's actions have been in accordance with the applicable positive legal provisions and reflect the flexibility of the law in modern corporate practice